Growth and Yield of Different Size-Seedling Tubers Derived from True Potato (Solanum tuberosum L.) Seeds as Influenced by Clump Planting (The Agriculturists, 2014)
An experiment was conducted at the Horticulture farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during November 2010 to March 2011. Four levels of seedling tuber size, viz. 6-